2018
DOI: 10.1002/bdd.2122
|View full text |Cite
|
Sign up to set email alerts
|

Verification of a physiologically based pharmacokinetic model of ritonavir to estimate drug–drug interaction potential of CYP3A4 substrates

Abstract: Ritonavir is one of several ketoconazole alternatives used to evaluate strong CYP3A4 inhibition potential in clinical drug-drug interaction (DDI) studies. In this study, four physiologically based pharmacokinetic (PBPK) models of ritonavir as an in vivo time-dependent inhibitor of CYP3A4 were created and verified for oral doses of 20, 50, 100 and 200 mg using the fraction absorbed (F ) and oral clearance (CL ) values reported in the literature, because transporter and CYP enzyme reaction phenotyping data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Based on ultrasound imaging, Ramsay et al [25] reported the presence of an average nine milk ducts (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] in the human breast, confirming reports of other investigators. The same study revealed milk duct diameters ranging between 1 and 4.4 mm.…”
Section: Anatomy Physiology and Cell Biology Of The Mammary Gland In Relation To Drug Milk Excretionmentioning
confidence: 57%
See 1 more Smart Citation
“…Based on ultrasound imaging, Ramsay et al [25] reported the presence of an average nine milk ducts (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] in the human breast, confirming reports of other investigators. The same study revealed milk duct diameters ranging between 1 and 4.4 mm.…”
Section: Anatomy Physiology and Cell Biology Of The Mammary Gland In Relation To Drug Milk Excretionmentioning
confidence: 57%
“…Nevertheless, combining nonclinical data with PBPK modelling and simulation [6], is emerging as a powerful strategy to make reliable and quantitative predictions of in vivo drug behavior. Such a strategy has for instance been applied repeatedly for quantitative prediction of numerous drug-drug interactions ( [7][8][9][10][11][12][13][14][15][16]) or drug disposition in specific populations (e.g. pediatrics) [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Since RTV is the only clinical inhibitor and inducer of CYP3A4 within the regimen, only RTV was simulated as a surrogate for the RTV-containing regimens [35]. In addition, the PBPK model of RTV has been already verified by simulating its inhibition effects on the PK profiles of CYP3A4 substrates [36]. Thus, the RTV model was not herein verified.…”
Section: Nifedipine-rtv Ddi Predictionmentioning
confidence: 99%
“…RTV, an antiretroviral drug, is a strong inhibitor of intestinal and hepatic CYP3A4/5 and gut P‐glycoprotein (P‐gp), and is used to evaluate the maximal CYP3A inhibition potential of substrates in clinical DDI studies. 13 , 14 Grapefruit juice is a strong inhibitor of intestinal but not hepatic CYP3A4/5, allowing differentiation when compared to the RTV results. 15 , 16 Remibrutinib was given orally; an intravenous microtracer was administered 2 h post‐remibrutinib in the form of a stable isotope labeled remibrutinib (SIL‐remibrutinib).…”
Section: Introductionmentioning
confidence: 99%